Prevalence of Conventional Risk Factors and Lipid Profiles of Patients with First Day of Acute Coronary Syndrome Admitted in CCU of Gandaki Medical College Teaching Hospital, Pokhara, Nepal - Hirachan, Gopi Prasad; Hirachan, R; Thapa, BB; Thapa, KB (Journal of Gandaki Medical College-Nepal, 2017)
Background: Out of the total number of patients admitted in coronary care unit (CCU) with acute coronary syndrome (ACS), 75 - 85% presented with conventional risk factors. On the other hand, lipid profile modification after a cardiovascular event related to acute coronary syndrome has also been recognized. But there are controversies regarding the temporary changes in lipid profile after ACS. In our country, there are limited studies about the basal characteristics of lipid profile and the variability of its components after an ACS. Objectives: 1) To analyze the changes in lipoprotein levels in a group of patients hospitalized with ACS. 2) To describe the basal lipid profile. 3) To find out the prevalence of conventional risk factors of ACS patients. Methods: A total of 300 patients with the diagnosis of ACS were studied and the presence of conventional risk factors including smoking, hypertension, dyslipidemia and diabetes were recorded. In addition, we also analyzed the lipid profile within the first 24 hours of admission and body mass index (BMI) of all the patients included in the study. Results: Among a total of 300 patients, the mean age of men was 45 – 75 years and women 50 – 65 years. There were 47.5% patients with non-STEMI and 52.5% with ST-elevated myocardial infaraction (STEMI). In patients with BMI <24, 23.9% were males and 32.2% females; in patients with BMI 25 - 29, 55.4% were males and 48.7% females and in patients with BMI >30, 20.7% were males and 19.1% females. Among the study population, prior myocardial infaraction (MI) was seen in 29%, prior CABG in 4.2% and 10.5% had family history of CAD. In this study, diabetes and dyslipidemia were more in STEMI whereas dyslipidemia was common in non-STEMI. Among the conventional risk factors, smoking and hypertension were more common in STEMI in both men and women. Conclusions: In all patients admitted in CCU, basal lipid profile should be evaluated at the time of admission for choosing the most adequate treatment. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, page: 13-16